A new species of Limnephilidae (Insecta: Trichoptera) from the Western Alps (Insecta: Trichoptera) - Graf, Wolfram; Vitecek, Simon (Zootaxa, 2016)
A new species of the alpine caddisfly genus Consorophylax (Trichoptera, Limnephilidae, Stenophylacini) and the female of the recently described C. vinconi Graf & Malicky 2015 are described. The new species C. lepontiorum sp. nov. is a microendemic of the Southwestern Alps and differs from its congeners in the shape of the superior and inferior appendages and the unique setation of the aedeagus, absent in all other Consorophylax species. The female of C. vinconi is characterized by the unique formation of the anal tube. Potential effects of alpine orogenesis, phenology and climatic oscillation on speciation of aquatic insects inhabiting high-altitude habitats are discussed. The description of C. lepontiorum sp. nov. accentuates the significance of watersheds in the Western Alps as harbours of aquatic insect biodiversity, and demonstrates the necessity of additional faunal and taxonomic studies in Europe—a supposedly well-explored region.